Influence of steric hindrance on the molecular packing and the anchoring of quinonoid zwitterions on gold surfaces. (22nd February 2016) - Yuan, Minghui; Tanabe, Iori; Bernard-Schaaf, Jean-Marie; Shi, Qin-Yin; Schlegel, Vicki; Schurhammer, Rachel; Dowben, Peter A.; Doudin, Bernard; Routaboul, Lucie; Braunstein, Pierre
Abstract : The N -substituent on quinonoid zwitterions influences the molecules packing and impacts their anchoring on gold surfaces. Abstract : Driven by the huge potential of engineering the molecular band offset with highly dipolar molecules for improving charge injection into organic electrics, the anchoring of various N -alkyl substituted quinonoid zwitterions of formula (R = iPr, Cy, CH2 CH(Et)CH2 CH2 CH2 CH3, …) on gold surfaces is studied. The N–Au interactions result in an orthogonal arrangement of the zwitterions cores with respect to the surface, and stabilize adsorbed compact rows of molecules. IR spectroscopy is used as a straightforward diagnostic tool to validate the presence of ultra-thin molecular films. When combined with computational studies, IR measurements indicate that the presence of a CH2 group in α position to the nitrogen atom is important for a successful anchoring through N–Au interactions. The presence of such a flexible CH2 spacer, or of aryl groups, enables π-interactions with the surface, making possible the anchoring of enantiopure or sterically-hindered zwitterions. X-ray diffraction analyses indicate that the intermolecular spacing within a row of molecules can be modulated by the nature of the alkyl substituent R. This modulation is directly relevant to the electronic properties of the corresponding molecular films since these zwitterions are expected to form rows on gold surfaces similar to those observed in the bulk crystalline state.